Nanozyme-based aptasensors for the detection of tumor biomarkers - Ke Wang; Xiaogang Lin; Xiao Lv; Mingna Xie; Jinyu Wu; Jie Jayne Wu; Yang Luo (Journal of Biological Engineering)
Abstract A nanozyme-based aptasensor combines the unique properties of nanozymes with the specificity of aptamers for the detection of various biomolecules. Nanozymes are nanomaterials that possess enzyme-like properties, demonstrating substantial potential for enhancing the sensing capabilities of biosensors. In recent years, the incorporation of nanozymes into biosensors has opened new avenues for the detection of tumor biomarkers. The unique attributes of nanozymes and aptamers lead to biosensors characterized by high sensitivity, specificity, reproducibility and accuracy in analytical performance. This article reviews the research progress of nanozyme-based aptasensors in tumor biomarker detection over the past decade. We categorize these sensors based on their sensing modes and target types, and examine the properties and applications of the nanozymes employed in these devices, providing a thorough discussion of the strengths and weaknesses associated with each sensor type. Finally, the review highlights the strengths and challenges associated with nanozyme-based biosensors and envisions future developments and applications in this field. The objective is to provide insights for improving biosensor performance in tumor biomarker detection, thereby contributing to advancements in precision cancer diagnosis and treatment.